The Analysis of Factors Related to the Incidence Of Low Birth Weight In dr. Ben Mboi Ruteng Hospital, Manggarai Regency - Reineldis Elsidianastika Trisnawati Neldis (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2021)
ABSTRACT LBW is considered the leading cause of infant mortality, especially in the first month of life. The incidence of LBW in Indonesia has a prevalence of 10.2% and most of the LBW infants who died during the neonatal period. According to the health profile of the East Nusa Tenggara Province, the number of infant mortality cases in NTT Province in 2018 was 1,265 cases, the factors causing infant mortality in this case were dominated by LBW and Asphyxia. Based on data obtained from dr. Ben Mboi Ruteng Hospital, LBW cases in 2019 totaled 640 cases. LBW is one of the risk factors that have a contribution to infant mortality during the neonatal period. Until now, LBW is still a problem that causes morbidity and mortality in newborns. The purpose of this study was to analyze the factors associated with the incidence of low birth weight babies (LBW) in dr.Ben Mboi Ruteng Hospital. This type of research is a quantitative study with a cross sectional research design. The population in the study was 2.480 mothers giving birth and the sample size obtained was 96 respondents with a sampling technique, namely purposive sampling. The results of statistical tests using Chi Square with a significance level of 0,05 indicate that maternal age has a p-value of 0,004 (p<0,05), gestational age has a p-value of 0,004 (p<0,05) and parity has a p-value value 0,704 (p>0,05. The conclusion of this study is that there is a significant relationship between maternal age and gestational age with the incidence of LBW and there is no relationship between parity and the incidence of LBW in dr. Ben Mboi Ruteng Hospital. Keywords: age, parity, gestational age, LBW